PENEGAKAN HUKUM TERHADAP MEMBANGUN BANGUNAN BERDASARKAN PERATURAN DAERAH KOTA SAMARINDA NOMOR 34 TAHUN 2004 TENTANG BANGUNAN DALAM WILAYAH KOTA SAMARINDA (STUDI PELANGGARAN BANGUNAN DI JALAN AHMAD YANI KOTA SAMARINDA) - Makrondji, Khairunnisah dan (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2018)
The obligation to maintain environmental harmony in individualsor businesses that are legal entities carry out building activities inaccordance with what is mandated by Article 41 paragraph (2) RegionalRegulation of Samarinda City Number 34 of 2004 concerning Buildings inSamarinda City Region. However, especially on Jalan Ahmad Yani thereare still places to build buildings that violate, every implementation ofbuilding activities must maintain the security, safety of buildings and theenvironment and should not interfere with the peace and safety of thesurrounding community. In connection with the foregoing, it is interestingto study Law Enforcement Against Building Buildings Based onSamarinda City Regulation Number 34 of 2004 concerning Buildings inthe Samarinda City Area (building violation studies on Jalan Ahmad YaniSamarinda City. How to enforce law and legal efforts against RegionalRegulation of Samarinda City Number 34 of 2004 concerning Buildings inSamarinda City Region.This research was carried out at the Samarinda One-StopIntegrated Licensing Service Agency, UPTD Operational Control UnitBuilding and places to build buildings on Jalan Ahmad Yani SamarindaCity. Collecting data with field studies, namely interviews andobservations / field observations, as well as library studies. Based on theresults of research in the field, it is shown that enforcement of places tobuild buildings that are not in accordance with environmentalpreservation on Ahmad Yani street in Samarinda City is not effective. Thiscan be seen from the fact that there are still a lot of stacking places thathave not implemented implementation that is in line with environmentalsustainability, which enforcement actions do not take place. Law enforcerswho are not strict in enforcing building activities that are not inaccordance with the procedures for making this Regional Regulation are not implemented. This can be seen from the fact that there is still a placeto build buildings that does not care about the sustainability of theenvironment when building a building, it can disrupt the comfort andsafety of the surrounding environment and the people who cross the area.